Black substrate-free grid exhaust heat-conducting double-sided adhesive tape

By using black baseless mesh exhaust thermal double-sided tape on the vehicle-mounted OLED display, using the combination of thermal filler and hyperbranched silicone modified polyurethane, the existing tape is solved inadequate thermal conductivity and humidity and heat resistance to aging. The poor problem achieves efficient thermal conductivity and long-life adhesiveness, which is suitable for the application of vehicle-mounted OLED displays.

CN119144270AActive Publication Date: 2024-12-17JIANGSU MINORU TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411093389.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2024-12-17
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

The existing grid exhaust thermal tape for automotive OLED display screens has problems such as poor adhesiveness, insufficient thermal conductivity, high temperature resistance and humidity and heat resistance to improve.

Method used

A black baseless mesh exhaust thermal double-sided tape is adopted, including a first mesh release layer, a thermal adhesive layer and a second mesh release layer, and the thermal adhesive layer is composed of a thermal filler, The flame retardant, black filler, hyperbranched silicone modified polyurethane and other components form an interpenetrating network structure through ultraviolet light and thermal curing to improve adhesion and thermal conductivity.

Benefits of technology

It achieves the effects of good adhesiveness, good thermal conductivity, high temperature resistance and humidity and heat aging resistance, reduces production costs and environmental risks, and is suitable for continuous large-scale production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a black substrate-free grid exhaust heat-conducting double-sided adhesive tape and a preparation method thereof. The black substrate-free grid exhaust heat-conducting double-sided adhesive tape comprises a first grid release layer, a heat-conducting adhesive layer and a second grid release layer which are sequentially stacked, the heat-conducting adhesive layer is prepared from the following raw materials: heat-conducting filler, a flame retardant, a dispersing agent, black filler, acrylate-terminated hyperbranched organic silicon modified polyurethane, a curing agent, 3-[N, N-dimethyl-[2-(2-methylpropyl-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt, 4-acryloyl benzophenone hydroxybenzoate, 2, 4, 6-trimethyl-1, 3-pentanedione, 2, 4, 6-trimethyl-1, 3-pentanedione, 2, 4, 6-trimethyl-1, 3-pentanedione, 2, 4, 6-trimethyl-1, 3-pentanedione, 2, 4-pentanedione The coating is prepared from the following raw materials in parts by weight: 1, 4-diacryloyl-1, 2, 3, 4-tetrahydro-6, 7-dimethyl quinoxaline, 2, 6-trivinyl boroxane, tris (2-acryloyloxyethyl) isocyanurate, tricyclic [5.2. 1.02, 6] deca-8-yl methacrylate, 1, 4-diacryloyl-1, 2, 3, 4-tetrahydro-6, 7-dimethyl quinoxaline, 2-vinylpyridine and a diluent. The double-sided adhesive tape is good in adhesion, good in heat-conducting property, and excellent in high-temperature resistance and damp-heat aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesive tapes, and in particular to a black substrate-free mesh exhaust heat-conducting double-sided adhesive tape. Background Art

[0002] With the development of display technology, OLED (organic light-emitting diode) display screens are becoming more and more popular, especially the use of automotive OLED display screens is becoming more and more widespread. However, in daily use, automotive OLED display screens are affected by the heat generated by the operation of the car, and the long-term high brightness state will also generate high heat. This heat is often not conducted away from the OLED display screen in time, thereby accelerating the aging of the organic materials of the OLED device, and then causing problems such as screen burn-in and uneven display. It is under this situation that the grid exhaust thermal conductive tape for automotive OLED display screens came into being, and its appearance has attracted widespread attention in the industry.

[0003] Most of the existing grid exhaust thermal conductive tapes for vehicle-mounted OLED displays use grid fibers as the tape base material, and then the glue is applied using a single-sided coating process. The preparation process is relatively complicated and the cost is relatively high. At the same time, the grid exhaust thermal conductive tapes for vehicle-mounted OLED displays on the market still have more or less technical defects such as poor adhesion, insufficient thermal conductivity, and high temperature resistance and moisture-heat aging resistance that need to be further improved.

[0004] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN115491135B discloses a high temperature resistant mesh acrylic pressure-sensitive adhesive tape and its preparation method, wherein the mesh acrylic pressure-sensitive adhesive tape comprises a mesh release film and a modified acrylic pressure-sensitive adhesive coated on the surface of the mesh release film; wherein the modified acrylic pressure-sensitive adhesive comprises, by weight, 20-30 parts of butyl acrylate, 18-24 parts of 2-ethylhexyl acrylate, 15-20 parts of 2-hydroxyethyl acrylate, 6.5-8.8 parts of octaaniline propyl caged polysilsesquioxane, 4.2-5.6 parts of acrylic acid amide scandium tungstate powder, 1.2-3.6 parts of initiator, 6-12 parts of the first solvent and 14-24 parts of the second solvent. The mesh acrylic pressure-sensitive adhesive tape finally obtained by the invention can improve the adhesiveness and high temperature peeling performance of the pressure-sensitive adhesive while maintaining a high peel strength. However, its resistance to wet heat aging and thermal conductivity still need to be further improved.

[0005] It can be seen that the development of a grid exhaust thermal conductive tape with good adhesion, good thermal conductivity, excellent high temperature resistance and excellent resistance to moisture and heat aging meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the field of tapes for automotive OLED displays. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a black substrate-free mesh exhaust thermal conductive double-sided tape with good adhesion, good thermal conductivity, excellent high temperature resistance and moisture-heat aging resistance, and sufficient light-shielding and adhesive surface adhesion and exhaust properties.

[0007] To achieve the above object, the technical scheme adopted by the present invention is: a black substrate-free mesh exhaust thermally conductive double-sided tape, comprising a first mesh release layer, a thermally conductive adhesive layer and a second mesh release layer stacked in sequence; the thermally conductive adhesive layer is made of the following raw materials in parts by weight: 20-50 parts of thermally conductive filler, 0-10 parts of flame retardant, 0.1-1 parts of dispersant, 0.1-5 parts of black filler, 20-40 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 0.1-1 parts of curing agent, 3-[N,N-dimethyl-[2-(2 -methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt 1-3 parts, 4-acryloylhydroxybenzoic acid benzophenone 1-3 parts, 2,4,6-trivinyl cycloboroxane 2-4 parts, tri(2-acryloyloxyethyl) isocyanurate 0.5-1.5 parts, methacrylate tricyclo[5.2.1.02,6]dec-8-yl ester 0.8-1.2 parts, 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline 0.3-0.6 parts, 2-vinylpyridine 1-3 parts, diluent 30-40 parts.

[0008] Preferably, the thermally conductive filler is any one or more of spherical alumina, hexagonal boron nitride, and aluminum nitride whiskers.

[0009] Preferably, the average particle size of the spherical aluminum oxide is 10-30 μm; the average particle size of the hexagonal boron nitride is 1-3 μm; the average particle size of the aluminum nitride whisker is 2-30 μm in diameter and 0.5-3 cm in length.

[0010] Preferably, the flame retardant is at least one of aluminum hydroxide flame retardant H-WF-10 and magnesium hydroxide flame retardant XS-MHB-3; the dispersant is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570.

[0011] Preferably, the black filler is at least one of carbon black, graphite, carbon nanotubes, and graphene; and the particle size of the black filler is 1000-1500 mesh.

[0012] Preferably, there is no special requirement for the source of the acrylate-terminated hyperbranched silicone-modified polyurethane. In one embodiment of the present invention, the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 in the authorization announcement number CN111393608B.

[0013] Preferably, the curing agent is a mixture of benzoin ethyl ether, azobisisobutyronitrile and benzoin isopropyl ether in a mass ratio of (1-3):(0.8-1.2):1.

[0014] Preferably, the diluent is a mixture of butyl acrylate, tripropylene glycol diacrylate, and 2-methoxyethyl acrylate in a mass ratio of (1-2):1:(1-3).

[0015] Preferably, the first grid release layer and the second grid release layer are independently made of PET release films with grid patterns.

[0016] Preferably, the mesh wall of the PET release film with a grid pattern is a convex shape, and its cross-section is one of a trapezoid, a triangle, an inverted U-shape, a rectangle, and a hemisphere; the mesh wall width is 4-20 μm, the mesh wall depth is 1-3 μm, and the distance between the mesh walls is 130-210 μm; the angle between the transverse and longitudinal mesh walls of the PET release film with a grid pattern is 90-180°.

[0017] Preferably, the thickness of the thermally conductive adhesive layer is 10-150 μm.

[0018] Another object of the present invention is to provide a method for preparing the black substrate-free mesh exhaust thermally conductive double-sided tape, comprising the following steps:

[0019] Step S1, mixing and stirring the raw materials of the thermal conductive adhesive layer according to parts by weight, ultrasonically dispersing, and vacuuming to remove bubbles to obtain a thermal conductive adhesive;

[0020] Step S2, evenly apply the thermally conductive adhesive prepared in step S1 on the first grid release layer, cover the thermally conductive adhesive layer with a second grid release layer, expose it to ultraviolet light, and then bake it at 50-70°C for 3-6 minutes to obtain a black substrate-free grid exhaust thermally conductive double-sided tape after curing.

[0021] Preferably, the wavelength of the ultraviolet light is 300-400 nm, and the irradiation time is 3-5 min.

[0022] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0023] (1) The method for preparing the black substrate-free mesh exhaust thermal conductive double-sided tape disclosed in the present invention has a simple process, convenient operation and control, high preparation efficiency and finished product qualification rate, no need for special equipment, low capital investment, low energy consumption, and no addition of any organic solvent, thus avoiding the safety hazards of using organic solvents as diluents, while reducing the cost of organic solvent investment, having better environmental protection, being suitable for continuous large-scale production, and having high promotion and application value.

[0024] (2) The black substrate-free mesh exhaust thermal double-sided tape disclosed in the present invention is provided with a first mesh release layer and a second mesh release layer, so that the gas can be easily discharged when the double-sided tape is attached to the object, thereby improving the product yield; the introduction of black filler greatly improves the overall shielding property of the tape, and when used in a vehicle-mounted OLED display screen, it can improve the light leakage phenomenon at the edge of the OLED display screen; the use of a substrate-free structure has a higher thermal conductivity coefficient due to the lack of the thermal resistance effect of the substrate.

[0025] (3) The black substrate-free mesh exhaust thermally conductive double-sided adhesive tape disclosed in the present invention, wherein the thermally conductive adhesive layer is made of the following raw materials in parts by weight: 20-50 parts of thermally conductive filler, 0-10 parts of flame retardant, 0.1-1 parts of dispersant, 0.1-5 parts of black filler, 20-40 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 0.1-1 parts of curing agent, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1- 1-3 parts of sulfonic acid salt, 1-3 parts of 4-acryloylhydroxybenzoic acid benzophenone, 2-4 parts of 2,4,6-trivinyl cycloboroxane, 0.5-1.5 parts of tris(2-acryloyloxyethyl) isocyanurate, 0.8-1.2 parts of tricyclo[5.2.1.02,6]dec-8-yl methacrylate, 0.3-0.6 parts of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 1-3 parts of 2-vinylpyridine, and 30-40 parts of diluent. Through the reasonable selection of the raw material formula for preparing the thermal conductive adhesive layer, the raw materials can better cooperate with each other, so that the double-sided adhesive product has good adhesion, good thermal conductivity, excellent high temperature resistance and moisture-heat aging resistance, and sufficient light-shielding and adhesive surface bonding and exhaust properties. Through ultraviolet light and thermal curing, not only an interpenetrating network structure is formed in the molecular structure of the glue, but also hyperbranched silicone-modified polyurethane, amphoteric organic ion salts, benzophenone, boroxine, isocyanurate, quinoxaline and pyridine groups are introduced. These structures and groups, under the multiple effects of electronic effect, steric effect and conjugation effect, make the product have better bonding performance, form more effective thermal bridges, better thermal conductivity, better high temperature resistance and heat aging resistance, and longer service life. DETAILED DESCRIPTION

[0026] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0027] Example 1

[0028] A black substrate-free mesh exhaust heat-conducting double-sided adhesive tape comprises a first mesh release layer, a heat-conducting adhesive layer and a second mesh release layer which are sequentially stacked; the heat-conducting adhesive layer is made of the following raw materials in parts by weight: 20 parts of heat-conducting filler, 1 part of flame retardant, 0.1 part of dispersant, 1 part of black filler, 20 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 0.1 part of curing agent, 3-[N,N-dimethyl-[2-(2-methylpropane-2- 1 part of [(2-acryloyloxyethyl)ammonium]propane-1-sulfonic acid inner salt, 1 part of 4-acryloylhydroxybenzoic acid benzophenone, 2 parts of 2,4,6-trivinyl cycloboroxane, 0.5 parts of tris(2-acryloyloxyethyl)isocyanurate, 0.8 parts of tricyclo[5.2.1.02,6]dec-8-yl methacrylate, 0.3 parts of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 1 part of 2-vinylpyridine, and 30 parts of diluent.

[0029] The thermal conductive filler is spherical alumina; the average particle size of the spherical alumina is 10 μm; the flame retardant is aluminum hydroxide flame retardant H-WF-10; the dispersant is silane coupling agent KH550; the black filler is carbon black; and the particle size of the black filler is 1000 mesh.

[0030] The acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 in the authorization announcement number CN111393608B; the curing agent is a mixture of benzoin ethyl ether, azobisisobutyronitrile, and benzoin isopropyl ether in a mass ratio of 1:0.8:1; the diluent is a mixture of butyl acrylate, tripropylene glycol diacrylate, and 2-methoxyethyl acrylate in a mass ratio of 1:1:1.

[0031] The first grid release layer and the second grid release layer are independently made of PET release films with grid patterns; the mesh wall of the PET release film with a grid pattern is a convex shape, and its cross-section is a trapezoid; the mesh wall width is 4μm, the mesh wall depth is 1μm, and the distance between the mesh walls is 130μm; the angle between the transverse and longitudinal mesh walls of the PET release film with a grid pattern is 90°; the thickness of the thermally conductive adhesive layer is 80μm.

[0032] A method for preparing the black substrate-free mesh exhaust heat-conductive double-sided adhesive tape comprises the following steps:

[0033] Step S1, mixing and stirring the raw materials of the thermal conductive adhesive layer according to parts by weight, ultrasonically dispersing, and vacuuming to remove bubbles to obtain a thermal conductive adhesive;

[0034] Step S2, evenly coating the thermally conductive adhesive prepared in step S1 on the first grid release layer, and covering the thermally conductive adhesive layer with a second grid release layer, irradiating it under ultraviolet light, and then baking it at 50°C for 3 minutes, and after curing, obtaining a black substrate-free grid exhaust thermally conductive double-sided tape; the wavelength of the ultraviolet light is 365nm, and the irradiation time is 4min.

[0035] Example 2

[0036] A black substrate-free mesh exhaust heat-conducting double-sided adhesive tape, comprising a first mesh release layer, a heat-conducting adhesive layer and a second mesh release layer stacked in sequence; the heat-conducting adhesive layer is made of the following raw materials in parts by weight: 30 parts of heat-conducting filler, 5 parts of flame retardant, 0.3 parts of dispersant, 2 parts of black filler, 25 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 0.3 parts of curing agent, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy] )ethyl]ammonium]propane-1-sulfonic acid inner salt 1.5 parts, 4-acryloylhydroxybenzoic acid benzophenone 1.5 parts, 2,4,6-trivinyl cycloboroxine 2.5 parts, tri(2-acryloyloxyethyl)isocyanurate 0.8 parts, methacrylate tricyclo[5.2.1.02,6]dec-8-yl ester 0.9 parts, 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline 0.4 parts, 2-vinylpyridine 1.5 parts, diluent 32 parts.

[0037] The thermal conductive filler is hexagonal boron nitride; the hexagonal boron nitride is 1.5 μm; the flame retardant is magnesium hydroxide flame retardant XS-MHB-3; the dispersant is silane coupling agent KH560; the black filler is graphite; and the particle size of the black filler is 1100 mesh.

[0038] The acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 in the authorization announcement number CN111393608B; the curing agent is a mixture of benzoin ethyl ether, azobisisobutyronitrile, and benzoin isopropyl ether in a mass ratio of 1.5:0.9:1; the diluent is a mixture of butyl acrylate, tripropylene glycol diacrylate, and 2-methoxyethyl acrylate in a mass ratio of 1.2:1:1.5.

[0039] The first grid release layer and the second grid release layer are independently made of PET release films with grid patterns; the mesh wall of the PET release film with a grid pattern is a convex shape, and its cross-section is a triangle; the mesh wall width is 10μm, the mesh wall depth is 1.5μm, and the distance between the mesh walls is 150μm; the angle between the transverse and longitudinal mesh walls of the PET release film with a grid pattern is 110°; the thickness of the thermally conductive adhesive layer is 80μm.

[0040] A method for preparing the black substrate-free mesh exhaust heat-conductive double-sided adhesive tape comprises the following steps:

[0041] Step S1, mixing and stirring the raw materials of the thermal conductive adhesive layer according to parts by weight, ultrasonically dispersing, and vacuuming to remove bubbles to obtain a thermal conductive adhesive;

[0042] Step S2, uniformly coating the thermal conductive adhesive prepared in step S1 on the first grid release layer, and covering the thermal conductive adhesive layer with a second grid release layer, irradiating under ultraviolet light, and then baking at 55°C for 4 minutes, and obtaining a black substrate-free grid exhaust thermal double-sided tape after curing; the wavelength of the ultraviolet light is 365nm, and the irradiation time is 4min. .

[0043] Example 3

[0044] A black substrate-free mesh exhaust heat-conducting double-sided adhesive tape, comprising a first mesh release layer, a heat-conducting adhesive layer and a second mesh release layer stacked in sequence; the heat-conducting adhesive layer is made of the following raw materials in parts by weight: 35 parts of heat-conducting filler, 6 parts of flame retardant, 0.6 parts of dispersant, 3.5 parts of black filler, 30 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 0.6 parts of curing agent, 3-[N,N-dimethyl-[2-(2-methyl-acrylic acid] -2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt 2 parts, 4-acryloylhydroxybenzoic acid benzophenone 2 parts, 2,4,6-trivinyl cycloboroxane 3 parts, tris(2-acryloyloxyethyl) isocyanurate 1 part, methacrylate tricyclo[5.2.1.02,6]dec-8-yl ester 1 part, 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline 0.45 parts, 2-vinylpyridine 2 parts, diluent 35 parts.

[0045] The thermal conductive filler is aluminum nitride whisker; the diameter of the aluminum nitride whisker is 10 μm and the length is 1 cm; the flame retardant is aluminum hydroxide flame retardant H-WF-10; the dispersant is silane coupling agent KH570; the black filler is nano carbon tube; the particle size of the black filler is 1300 mesh.

[0046] The acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 in the authorization announcement number CN111393608B; the curing agent is a mixture of benzoin ethyl ether, azobisisobutyronitrile, and benzoin isopropyl ether in a mass ratio of 2:1:1; the diluent is a mixture of butyl acrylate, tripropylene glycol diacrylate, and 2-methoxyethyl acrylate in a mass ratio of 1.5:1:2.

[0047] The first grid release layer and the second grid release layer are independently made of PET release films with grid patterns; the mesh wall of the PET release film with a grid pattern is a convex shape, and its cross-section is an inverted U shape; the mesh wall width is 12μm, the mesh wall depth is 2μm, and the distance between the mesh walls is 170μm; the angle between the transverse and longitudinal mesh walls of the PET release film with a grid pattern is 130°; the thickness of the thermally conductive adhesive layer is 80μm.

[0048] A method for preparing the black substrate-free mesh exhaust heat-conductive double-sided adhesive tape comprises the following steps:

[0049] Step S1, mixing and stirring the raw materials of the thermal conductive adhesive layer according to parts by weight, ultrasonically dispersing, and vacuuming to remove bubbles to obtain a thermal conductive adhesive;

[0050] Step S2, uniformly coating the thermally conductive adhesive prepared in step S1 on the first grid release layer, and covering the thermally conductive adhesive layer with a second grid release layer, irradiating the layer under ultraviolet light, and then baking the layer at 60° C. for 4.5 minutes to obtain a black substrate-free grid exhaust thermally conductive double-sided tape after curing; the wavelength of the ultraviolet light is 365 nm, and the irradiation time is 4 min.

[0051] Example 4

[0052] A black substrate-free mesh exhaust heat-conducting double-sided adhesive tape, comprising a first mesh release layer, a heat-conducting adhesive layer and a second mesh release layer stacked in sequence; the heat-conducting adhesive layer is made of the following raw materials in parts by weight: 45 parts of heat-conducting filler, 9 parts of flame retardant, 0.8 parts of dispersant, 4 parts of black filler, 35 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 0.8 parts of curing agent, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy] )ethyl]ammonium]propane-1-sulfonic acid inner salt 2.5 parts, 4-acryloylhydroxybenzoic acid benzophenone 2.5 parts, 2,4,6-trivinyl cycloboroxine 3.5 parts, tri(2-acryloyloxyethyl)isocyanurate 1.3 parts, methacrylate tricyclo[5.2.1.02,6]dec-8-yl ester 1.1 parts, 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline 0.55 parts, 2-vinylpyridine 2.5 parts, diluent 38 parts.

[0053] The thermal conductive filler is a mixture of spherical aluminum oxide, hexagonal boron nitride, and aluminum nitride whiskers in a mass ratio of 1:2:1; the average particle size of the spherical aluminum oxide is 20 μm; the hexagonal boron nitride is 2 μm; the diameter of the aluminum nitride whisker is 5 μm and the length is 0.5 cm; the flame retardant is a mixture of aluminum hydroxide flame retardant H-WF-10 and magnesium hydroxide flame retardant XS-MHB-3 in a mass ratio of 3:5; the dispersant is a mixture of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570 in a mass ratio of 1:3:5; the black filler is a mixture of carbon black, graphite, carbon nanotubes, and graphene in a mass ratio of 1:1:3:2; the particle size of the black filler is 1400 mesh.

[0054] The acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 in the authorization announcement number CN111393608B; the curing agent is a mixture of benzoin ethyl ether, azobisisobutyronitrile, and benzoin isopropyl ether in a mass ratio of 2.5:1.1:1; the diluent is a mixture of butyl acrylate, tripropylene glycol diacrylate, and 2-methoxyethyl acrylate in a mass ratio of 1.8:1:2.5.

[0055] The first grid release layer and the second grid release layer are independently made of PET release films with grid patterns; the mesh wall of the PET release film with a grid pattern is convex in shape and has a rectangular cross-section; the mesh wall width is 18 μm, the mesh wall depth is 2.5 μm, and the distance between the mesh walls is 200 μm; the angle between the transverse and longitudinal mesh walls of the PET release film with a grid pattern is 160°; the thickness of the thermally conductive adhesive layer is 80 μm.

[0056] A method for preparing the black substrate-free mesh exhaust heat-conductive double-sided adhesive tape comprises the following steps:

[0057] Step S1, mixing and stirring the raw materials of the thermal conductive adhesive layer according to parts by weight, ultrasonically dispersing, and vacuuming to remove bubbles to obtain a thermal conductive adhesive;

[0058] Step S2, evenly coating the thermally conductive adhesive prepared in step S1 on the first grid release layer, and covering the thermally conductive adhesive layer with a second grid release layer, irradiating it under ultraviolet light, and then baking it at 65°C for 5 minutes, and after curing, obtaining a black substrate-free grid exhaust thermally conductive double-sided tape; the wavelength of the ultraviolet light is 365nm, and the irradiation time is 4min.

[0059] Example 5

[0060] A black substrate-free mesh exhaust heat-conducting double-sided adhesive tape, comprising a first mesh release layer, a heat-conducting adhesive layer and a second mesh release layer stacked in sequence; the heat-conducting adhesive layer is made of the following raw materials in parts by weight: 50 parts of heat-conducting filler, 10 parts of flame retardant, 1 part of dispersant, 5 parts of black filler, 40 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 1 part of curing agent, 3-[N,N-dimethyl-[2-(2-methylprop-2-ene] 3 parts of [(2-acryloyloxyethyl)]ammonium]propane-1-sulfonic acid inner salt, 3 parts of 4-acryloylhydroxybenzoic acid benzophenone, 4 parts of 2,4,6-trivinyl cycloboroxine, 1.5 parts of tris(2-acryloyloxyethyl)isocyanurate, 1.2 parts of tricyclo[5.2.1.02,6]dec-8-yl methacrylate, 0.6 parts of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 3 parts of 2-vinylpyridine, and 40 parts of diluent.

[0061] The thermal conductive filler is spherical alumina; the average particle size of the spherical alumina is 30 μm; the flame retardant is aluminum hydroxide flame retardant H-WF-10; the dispersant silane coupling agent KH560; the black filler is graphite; the particle size of the black filler is 1500 mesh; the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 in the authorization announcement number CN111393608B; the curing agent is a mixture of benzoin ethyl ether, azobisisobutyronitrile, and benzoin isopropyl ether in a mass ratio of 3:1.2:1; the diluent is a mixture of butyl acrylate, tripropylene glycol diacrylate, and 2-methoxyethyl acrylate in a mass ratio of 2:1:3.

[0062] The first grid release layer and the second grid release layer are independently made of PET release films with grid patterns; the mesh wall of the PET release film with a grid pattern is convex in shape, and its cross-section is hemispherical; the mesh wall width is 20 μm, the mesh wall depth is 3 μm, and the distance between the mesh walls is 210 μm; the angle between the transverse and longitudinal mesh walls of the PET release film with a grid pattern is 180°; the thickness of the thermally conductive adhesive layer is 80 μm.

[0063] A method for preparing the black substrate-free mesh exhaust heat-conductive double-sided adhesive tape comprises the following steps:

[0064] Step S1, mixing and stirring the raw materials of the thermal conductive adhesive layer according to parts by weight, ultrasonically dispersing, and vacuuming to remove bubbles to obtain a thermal conductive adhesive;

[0065] Step S2, evenly coating the thermally conductive adhesive prepared in step S1 on the first grid release layer, and covering the thermally conductive adhesive layer with a second grid release layer, irradiating it under ultraviolet light, and then baking it at 70°C for 6 minutes, and after curing, obtaining a black substrate-free grid exhaust thermally conductive double-sided tape; the wavelength of the ultraviolet light is 365nm, and the irradiation time is 4min.

[0066] Comparative Example 1

[0067] A black substrate-free mesh exhaust thermally conductive double-sided tape and a preparation method thereof, which are substantially the same as those in Example 1, except that 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt and 1,4-diacryl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline are not added.

[0068] Comparative Example 2

[0069] A black substrate-free mesh exhaust thermally conductive double-sided adhesive tape and a preparation method thereof are substantially the same as those in Example 1, except that 2-vinylpyridine and 4-acryloylhydroxybenzoic acid benzophenone are not added.

[0070] In order to further illustrate the beneficial technical effects of the black substrate-free mesh exhaust thermally conductive double-sided tape involved in each embodiment of the present invention, relevant performance tests were conducted on the black substrate-free mesh exhaust thermally conductive double-sided tape involved in Examples 1-5 and Comparative Examples 1-2; the test method is as follows:

[0071] (1) Thermal conductivity: Refer to ASTM-D5470 for thermal conductivity test;

[0072] (2) Peel strength: 180 degree peel strength test of SUS steel plate was carried out according to GB / T2792-2014;

[0073] (3) Resistance to moisture and heat aging: Each example of black substrate-free mesh exhaust thermal double-sided tape was placed in an environment of 90°C and 95% relative humidity for 150 hours. After cooling to room temperature, the 180-degree peel strength was tested again according to the method in (2), and the retention rate of the 180-degree peel strength was calculated. The larger the value, the better the resistance to moisture and heat aging.

[0074] (4) High temperature resistance: The test samples were placed in an aging oven at 95°C for 1000 hours. After cooling to room temperature, the 180-degree peel strength was tested according to the method in (2). The retention rate of the 180-degree peel strength was calculated. The larger the value, the better the high temperature resistance.

[0075] (5) Fit and usability: Check visually for bubbles.

[0076] The UV curing equipment used in the above test is: LED UV curing lamp, model: XC210-YJ, light source wavelength: 365nm, UV intensity: 1000mW / CM 2 , irradiation time: 4min.

[0077] Table 1

[0078] Test items Thermal conductivity 180 degree peel strength Resistance to moisture and heat aging High temperature resistance Fit for use unit W / (m·K) N / cm % % — Example 1 0.99 12.0 99.23 99.41 No bubbles Example 2 1.18 12.3 99.35 99.50 No bubbles Example 3 1.06 12.5 99.55 99.63 No bubbles Example 4 1.35 12.6 99.70 99.83 No bubbles Example 5 1.30 13.1 99.81 99.95 No bubbles Comparative Example 1 0.83 9.5 95.49 96.62 No bubbles Comparative Example 2 0.92 10.8 97.76 98.05 No bubbles

[0079] As can be seen from Table 1, the black substrate-free mesh exhaust thermally conductive double-sided adhesive tapes prepared in various embodiments of the present invention have better thermal conductivity, bonding performance, moisture-heat aging resistance and high temperature resistance than the comparative example products, and have good fit and usability. The combined use of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 2-vinylpyridine and 4-acryloylhydroxybenzoic acid benzophenone is beneficial to improving the above-mentioned properties.

[0080] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A black substrate-free mesh exhaust thermal conductive double-sided tape, It is characterized in that The invention comprises a first grid release layer, a heat conductive adhesive layer and a second grid release layer which are sequentially stacked; the heat conductive adhesive layer is made of the following raw materials in parts by weight: 20-50 parts of heat conductive filler, 0-10 parts of flame retardant, 0.1-1 parts of dispersant, 0.1-5 parts of black filler, 20-40 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 0.1-1 parts of curing agent, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane -1-sulfonic acid inner salt 1-3 parts, 4-acryloylhydroxybenzoic acid benzophenone 1-3 parts, 2,4,6-trivinyl cycloboroxane 2-4 parts, tris (2-acryloyloxyethyl) isocyanurate 0.5-1.5 parts, methacrylate tricyclo [5.2.1.02,6] dec-8-yl ester 0.8-1.2 parts, 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline 0.3-0.6 parts, 2-vinyl pyridine 1-3 parts, diluent 30-40 parts.

2. The black substrate-free mesh exhaust thermally conductive double-sided tape according to claim 1, It is characterized in that The thermal conductive filler is any one or more of spherical aluminum oxide, hexagonal boron nitride, and aluminum nitride whiskers.

3. The black substrate-free mesh exhaust thermally conductive double-sided tape according to claim 2, It is characterized in that The average particle size of the spherical aluminum oxide is 10-30 μm; the average particle size of the hexagonal boron nitride is 1-3 μm; the average particle size of the aluminum nitride whisker is 2-30 μm in diameter and 0.5-3 cm in length.

4. The black substrate-free mesh exhaust thermally conductive double-sided tape according to claim 1, It is characterized in that The flame retardant is at least one of aluminum hydroxide flame retardant H-WF-10 and magnesium hydroxide flame retardant XS-MHB-3; the dispersant is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570.

5. The black substrate-free mesh exhaust thermally conductive double-sided tape according to claim 1, It is characterized in that The black filler is at least one of carbon black, graphite, carbon nanotubes and graphene; and the particle size of the black filler is 1000-1500 meshes.

6. The black substrate-free mesh exhaust thermally conductive double-sided tape according to claim 1, It is characterized in that The curing agent is prepared by mixing benzoin ethyl ether, azobisisobutyronitrile and benzoin isopropyl ether in a mass ratio of (1-3):(0.8-1.2):

1.

7. The black substrate-free mesh exhaust thermally conductive double-sided tape according to claim 1, It is characterized in that The diluent is a mixture of butyl acrylate, tripropylene glycol diacrylate and 2-methoxyethyl acrylate in a mass ratio of (1-2):1:(1-3).

8. The black substrate-free mesh exhaust thermally conductive double-sided tape according to claim 1, It is characterized in that The first grid release layer and the second grid release layer are independently made of PET release films with grid patterns; the mesh wall of the PET release film with a grid pattern is a convex shape, and its cross-section is one of a trapezoid, a triangle, an inverted U-shape, a rectangle, and a hemispherical shape; the mesh wall width is 4-20 μm, the mesh wall depth is 1-3 μm, and the distance between the mesh walls is 130-210 μm; the angle between the transverse and longitudinal mesh walls of the PET release film with a grid pattern is 90-180°.

9. The black substrate-free mesh exhaust thermally conductive double-sided tape according to claim 1, It is characterized in that The thickness of the thermal conductive adhesive layer is 10-150 μm.

10. A method for preparing the black substrate-free mesh exhaust thermal conductive double-sided adhesive tape according to any one of claims 1 to 9, It is characterized in that The steps include: Step S1, mixing and stirring the raw materials of the thermal conductive adhesive layer according to parts by weight, ultrasonically dispersing, and vacuuming to remove bubbles to obtain a thermal conductive adhesive; Step S2, uniformly coating the thermally conductive adhesive prepared in step S1 on the first grid release layer, and covering the thermally conductive adhesive layer with a second grid release layer, irradiating the layer under ultraviolet light, and then baking the layer at 50-70°C for 3-6 minutes to obtain a black substrate-free grid exhaust thermally conductive double-sided tape after curing; the wavelength of the ultraviolet light is 300-400nm, and the irradiation time is 3-5min.

Citation Information

Patent Citations

  • Adhesive composition adhesive adhesive sheet and display

    CN108690519A

  • Ultrathin single-sided grid PET double-sided adhesive tape and preparation method thereof

    CN111378394A

  • PU foam double-sided adhesive tape and preparation method thereof

    CN113652177A

  • Dispersion resin for LCD (Liquid Crystal Display) optical diffusion film and preparation method of dispersion resin

    CN117143290A

  • Organosilicon modified acrylic polyurethane prepolymer, optical adhesive composition, optical adhesive tape and preparation method and application thereof

    CN117777349A